Streptomyces alboflavus RPS and its novel and high algicidal activity against harmful algal bloom species Phaeocystis globosa. - Bangzhou Zhang; Guanjing Cai; Haitao Wang; Dong Li; Xujun Yang; Xinli An; Xiaowei Zheng; Yun Tian; Wei Zheng; Tianling Zheng (PLoS ONE)
Phaeocystis globosa blooms have frequently occurred along coastal waters and exerted serious impacts on ecological environments by releasing toxic hemolytic substances, forming nuisance foam, and causing oxygen depletion. An actinomycete strain RPS with high algicidal activity against P. globosa was isolated and identified as Streptomyces alboflavus, based on morphology, physiological and biochemical characteristics, and 16S rDNA sequence analysis. RPS lysed 95% of P. globosa within 48 h by releasing an extracellular active substance into the growth medium. The activity of RPS supernatant was sensitive to temperature at and above 50 °C and insensitive to pH from 3 to 11. The molecular weight of the active substance was between 100 Da and 1000 Da, and approximately 90% of it was extracted by ethyl acetate. It was presumed that the active component efficiently inhibited the movement of P. globosa, caused the flagella to fall off the algae, and finally lysed the algal cells. RPS showed a wide target range against harmful algae. S. alboflavus RPS with high algicidal activity and such novel features of temperature and pH sensitivity, low molecular weight, algicidal process, and target range possesses great potential in the biological control of P. globosa blooms.